2015
DOI: 10.1002/jbm.b.33542
|View full text |Cite
|
Sign up to set email alerts
|

Behavior of bone cells in contact with magnesium implant material

Abstract: Magnesium-based implants exhibit several advantages, such as biodegradability and possible osteoinductive properties. Whether the degradation may induce cell typespecific changes in metabolism still remains unclear. To examine the osteoinductivity mechanisms, the reaction of bone-derived cells (MG63, U2OS, SaoS2, and primary human osteoblasts (OB)) to magnesium (Mg) was determined. Mg-based extracts were used to mimic more realistic Mg degradation conditions. Moreover, the influence of cells having direct cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 37 publications
1
31
0
Order By: Relevance
“…Similar in vitro systems have been used by others. 6,7,21 The results of XPS-analysis of Mg, MgO, and MgCO 3 after incubation for 72 h in tissue culture medium are shown in Fig. 5.…”
Section: Resultsmentioning
confidence: 99%
“…Similar in vitro systems have been used by others. 6,7,21 The results of XPS-analysis of Mg, MgO, and MgCO 3 after incubation for 72 h in tissue culture medium are shown in Fig. 5.…”
Section: Resultsmentioning
confidence: 99%
“…This dynamic tissue‐implant interface is of special interest when evaluating biocompatibility, as here the cells or tissues come into direct contact with the material or its degradation products. In addition, changes in physiological parameters, such as pH, ion concentrations and so forth, may trigger unwanted physiological reactions …”
Section: In Vivo Testing Of Magnesium Alloysmentioning
confidence: 99%
“…21,[32][33][34][35] Notably, magnesium alloy extracts increase the pH of medium in which they are incubated; they also release potentially toxic ions and increase the osmolality. L929 cells can balance extracellular pH and osmolality to a certain extent 36 ; however, the high osmolality of magnesium alloy extracts can cause hyperosmotic shock in the first hours after the growth medium is replaced with extract. 37 Osmolality >500 mOsm kg 21 causes apoptosis, 38 and lower values might impact cell viability.…”
Section: Cell Culture Assaysmentioning
confidence: 99%
See 1 more Smart Citation
“…This natural function of osteoblasts might be influenced by the presence of a degradable implant [36] [39]. Recent investigations have shown that magnesium (Mg) itself has the capacity to stimulate the osteoblasts and to induce osteoinductive properties [37][38][39][40] [40][41][42][43]. However, the rapid degradation rate of Mg remains a critical challenge.…”
mentioning
confidence: 99%